Emerging Technologies and Information Systems for the Knowledge Society - Lytras, M.D. (Springer, 2017)
This book, in conjunction with the volume CCIS 19, constitutes the refereed proceedings of theFirst World Summit, WSKS 2008, held in Athens, Greece, in September 2008. The 64 revised full papers presented were carefully reviewed and selected from 286 submissions. The papers are organized in topical sections on social & humanistic computing for the knowledge society; knowledge, learning, education, learning technologies and e-learning for the knowledge society; information technologies for the knowledge society; culture & cultural heritage - technology for culture management - management of tourism and entertainment - tourism networks in the knowledge society; government and democracy for the knowledge society.